IMPACT OF TRADE LIBERALISATION REGIME AND ECONOMIC GROWTH IN NIGERIA - Adeniwura, Oluwatoba Oyedele; Onanuga, Abayomi Toyin; Adelowokan, Oluwaseyi Adedayo (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2025)
Introduction: This study aims to examine the impact of trade liberalization on economic growth in Nigeria, considering different policy regimes from 1986 to 2022. The study seeks to assess how exchange rates, capital stock, and policy shifts influenced economic growth during the Structural Adjustment Program (SAP) era and the gradual trade liberalization period. Methods: The linear regression model was employed with data sourced from the Central Bank of Nigeria publications and the National Bureau of Statistics. The Augmented Dickey-Fuller (ADF) test is used to test variable stationarity, and the Markov Switching Regime model captures the effects of policy shifts on economic growth. Results: In the first regime (SAP era), exchange rate and capital stock had a significant positive impact on economic growth, while trade liberalization showed a negative but insignificant effect. In the second regime (gradual trade liberalization), capital stock maintained a positive effect, but both trade liberalization and exchange rates had a significant negative impact. Conclusion and suggestion: The findings suggest that trade liberalization has had a generally negative impact on Nigeria's economic growth, particularly during the gradual liberalization period. To promote growth, policymakers should reconsider the export promotion strategies that enhance domestic production.